The Effect of Concept Mapping Approach on Scientific Attitude and Achievement in Science among Students with Learning Disability - Singh, Anu; Rahman, Saifur (JOURNAL OF INDIAN EDUCATION, 2024)
Students with dyslexia must be equipped with means to develop their metacognitive capacities especially the ‘learning to learn’ skills for effective lifelong learning. Concept Mapping is one such teaching approach and this study aims to determine the effectiveness of this approach on scientific attitude and achievement in science among students with dyslexia. A two group, pre-test or post-test, quasi-experimental design was employed, where 35 dyslexic students of Class VI studying in government schools of Chandigarh were selected, and randomly assigned to control and experimental groups. The control group consisted of 18 students, 10 boys and 8 girls, who received conventional teaching whereas the experimental group consisted of 17 students, 8 boys and 9 girls who received teaching via Concept Mapping Approach for a period of 20 days. Their scores were measured on SAS-KAGS by Kaur and Gakhar and SAT by the researcher herself. Analysis of pre- and post-test data revealed that the Concept Mapping Approach is more effective in improving achievement in science, scientific attitude as well as retention of learned knowledge among dyslexic students as compared to conventional teaching method. It was also found that there exists a positive correlation between scientific attitude and achievement in science among these students.